The leniency rule revisited: Experiments on cartel formation with open communication - Maximilian Andres; Lisa Verena Bruttel; Jana Friedrichsen (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
The experimental literature on antitrust enforcement provides robust evidence that communication plays an important role for the formation and stability of cartels. We extend these studies through a design that distinguishes between innocuous communication and communication about a cartel, sanctioning only the latter. To this aim, we introduce a participant in the role of the competition authority, who is properly incentivized to judge communication content and price setting behavior of the firms. Using this novel design, we revisit the question whether a leniency rule successfully destabilizes cartels. In contrast to existing experimental studies, we find that a leniency rule does not affect cartelization. We discuss potential explanations for this contrasting result.
Keywords: C92; D43; L41; 330; cartel; judgment of communication; corporate leniency program; price competition; experiment